Women's Participation in Sports (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This article analyzes the issue of women's participation in sports games. On a global scale, the development of women's sports, its history, state and prospects for today are studied. Based on the analysis of available literature, the social, economic and cultural aspects of women's sports are considered. The results are aimed at identifying the importance of women's sports, its impact on gender equality in society and existing problems. The article concluded with recommendations for the further development of women's activities in the field of sports.